2021
DOI: 10.1136/bmjopen-2020-040214
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and urinary albumin-creatinine ratio in the middle-aged and elderly population of Southern and Northern China: a cross-sectional study

Abstract: ObjectiveThe relationship between obesity and albuminuria has not been clarified. This study aimed to investigate the correlation between obesity and the urinary albumin-creatinine ratio (UACR) in Southern and Northern China.DesignA descriptive, cross-sectional study.SettingEight regional centres in REACTION (China’s Risk Evaluation of cAncers in Chinese diabeTic Individuals, a lONgitudinal study), including Dalian, Lanzhou, Zhengzhou, Guangzhou, Guangxi, Luzhou, Shanghai and Wuhan.ParticipantsA total of 41 08… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Several reports have suggested that age is an important risk factor for CKD [ 11 ]. The present study also revealed that the prevalence of CKD was significantly and positively associated with age, and also suggested a positive relationship of LAP quartiles with risk of CKD prevalence in subjects aged ≥60 years but not those aged < 60 years, which was similar to a previous study [ 27 ]. These results suggest older age might be associated with CKD prevalence because elderly individuals have higher prevalenceof comorbidities, such as obesity, hyperuricaemia, dyslipidaemia, diabetes, and hypertension, and more use of medications for these chronic diseases, which may have a profound negative impact on kidney function.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several reports have suggested that age is an important risk factor for CKD [ 11 ]. The present study also revealed that the prevalence of CKD was significantly and positively associated with age, and also suggested a positive relationship of LAP quartiles with risk of CKD prevalence in subjects aged ≥60 years but not those aged < 60 years, which was similar to a previous study [ 27 ]. These results suggest older age might be associated with CKD prevalence because elderly individuals have higher prevalenceof comorbidities, such as obesity, hyperuricaemia, dyslipidaemia, diabetes, and hypertension, and more use of medications for these chronic diseases, which may have a profound negative impact on kidney function.…”
Section: Discussionsupporting
confidence: 91%
“…Emerging epidemiologic studies have suggested that diabetes, hypertension, and dyslipidaemia are important risk factors for CKD [ 1 , 4 , 6 , 27 29 ]. Thepresent study also showed that male and female subjects with CKD had significantly more users of hypoglycaemic drugs, higher blood glucose (FBG, PBG, and HbA1c), prevalence of T2DM and hypertension compared with those without CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that hypertriglyceridemia or low HDL-C levels are only significantly associated with the development of CKD in patients with metabolic syndrome ( 32 , 44 ). Regarding central obesity, a longitudinal study in China found that people with both central and peripheral obesity had higher risks of elevated urine albumin-creatinine ratio, even after adjusting for multiple factors (OR: 1.14, 95% CI: 1.07–1.21, p < 0.001) ( 45 ). However, there is no consensus on the role of central obesity in the development of CKD ( 33 , 35 , 44 , 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Many studies have shown that obese people are more prone to increased UACR, and obesity is closely related to the risk of CKD progressing to end stage kidney disease (ESKD). 9,10 Obesity can also participate in the whole process of increased urinary protein excretion, occurrence and progression of CKD to ESKD through the indirect effect of related metabolic abnormalities caused by obesity. There is a causal relationship between obesity and the risk of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese Diabetes Cancer Risk Cohort Study (REACTION study) also found that obesity was significantly associated with a higher risk of elevated UACR, but unlike this study, the association was not significant in simple abdominal obesity people or simple systemic obesity people. 10 Given that the REACTION study excluded people with a diagnosis of CKD, and the REACTION study was based on the ratio of UACR to the median UACR in each sub-center population not directly study the level of UACR, we still believe that abdominal obesity is associated with increased UACR.…”
mentioning
confidence: 99%